Evaluasi Penigkatan Curah Hujan Untuk Mitigasi Bencana Kebakaran Lahan Gambut Dengan Teknologi Modifikasi Cuaca Di Kabupaten Bengkalis - Mutia Ananda Perdana; Sigit Sutikno; Ari Sandhyavitri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The peat fires disaster occurring on the island, particularly in Riau every year, which has at least adversely affected the environment, social and economic conditions of the community. One of the fire suppression effort is Autificial Rainfall (TMC), by sowing NaCl salts in clouds that have the potential for rain. This study piked up three regency areas in Riau Province, such as Bengkalis, Rokan Hilir and Dumai. With the data used is rainfall data from TRMMsatellite and fire distribution point data from fire forest watch. The data obtained were analyzed using FileZilla, GrADS, Command Prompt, and ArcMap V.10.1 software. The resultshows that, Autificial Rainfall (TMC) can accelerate the process of rainfall, thus the number of hotspots can be reduced. So this method can be used as a long-term program in disaster mitigation of peat fires.Keywords : TRMM, TMC, Hotspot